2019
DOI: 10.3171/2019.6.spine1963
|View full text |Cite
|
Sign up to set email alerts
|

Use of Patient Health Questionnaire–2 scoring to predict patient satisfaction and return to work up to 1 year after lumbar fusion: a 2-year analysis from the Michigan Spine Surgery Improvement Collaborative

Abstract: OBJECTIVEThe Michigan Spine Surgery Improvement Collaborative (MSSIC) is a prospective, longitudinal, multicenter, quality-improvement collaborative. Using MSSIC, the authors sought to identify the relationship between a positive Patient Health Questionnaire–2 (PHQ-2) screening, which is predictive of depression, and patient satisfaction, return to work, and achieving Oswestry Disability Index (ODI) minimal clinically important difference (MCID) scores up to 2 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The published literature demonstrates inconsistencies on the effect preoperative psychological disorders have on postoperative outcomes. While the vast majority of studies demonstrate a negative correlation between the presence of these conditions and objective and subjective outcomes, 6 , 17 , 18 , 30 - 60 large trials conflict these results. 61 - 68 Evaluating this disconcordant data may promote understanding of both current knowledge gaps and potential areas of future investigation.…”
Section: Resultsmentioning
confidence: 98%
“…The published literature demonstrates inconsistencies on the effect preoperative psychological disorders have on postoperative outcomes. While the vast majority of studies demonstrate a negative correlation between the presence of these conditions and objective and subjective outcomes, 6 , 17 , 18 , 30 - 60 large trials conflict these results. 61 - 68 Evaluating this disconcordant data may promote understanding of both current knowledge gaps and potential areas of future investigation.…”
Section: Resultsmentioning
confidence: 98%
“…These results were consistent with those from several previous studies 36–41 and may be explained by a complex interplay of factors involving (a) an altered motivational state (for exercise and activity), (b) executive-type cognitive impairments, and (c) the pathophysiological state of persistent low grade elevated inflammation associated with depression 38 . Given that depression, a potentially treatable condition, is often undiagnosed and untreated in patients with low back pain, 42 future research should consider identifying patients who may benefit from preoperative psychiatric optimization to improve lumbar fusion outcomes 43 …”
Section: Discussionmentioning
confidence: 99%
“…The association between preoperative depression and postoperative outcomes was demonstrated in previous studies ( 9 , 10 ). In a retrospective study of 8,585 patients, Zakaria et al ( 38 ) found that preoperative depression (measured using the Patient Health Questionnaire-2) predicted worse satisfaction and inability to return to work. In another retrospective study, Levin et al ( 9 ) analyzed the association between depression using the PHQ-9 and postoperative satisfaction after lumbar fusion.…”
Section: Discussionmentioning
confidence: 99%